Comparative strength of finger joint from Karas spp with pvac and contact adhesive / Ahmad Suhaidi Mohamed Suhaimi - Mohamed Suhaimi, Ahmad Suhaidi (Faculty of Applied Sciences, 2016)
The aim of this study was to identify whether the appropriate glue for installation at finger joint of karas spp. Type. of glue that will be used pvac and contact adhesive. Two glues were often used in the timber industry in Malaysia. This study was to supported the Malaysian timber species especially light hardwood and unused or excess wood from the waste or fuel. Size of finger joint is 2 cm wide, 2 cm thick and 300 cm length. With a difference of glue, the test will be conducted by using the testing machine. With the testing machine, the results showed pvac were stronger than contact adhesive glue. The statistical analysis results showed that pvac has a highest strength for the finger joint of the karas spp.